Physicochemical properties, strength and phytotoxicity of building blocks with waste cooking oil as binder. (10th February 2022) - Staroń, Anita; Papla, Aleksandra; Midura, Aleksandra; Kijania-Kontak, Magda; Świergosz, Tomasz; Banach, Marcin
Abstract: From year to year, the number of catering outlets, in particular fast-food restaurants, using oils increases, which causes a significant increase in the amount of oil waste generated. One potential use for waste cooking oil (WCO) is in the production of new forms of building materials. These new materials, where the cement binder is replaced with WCO, show high strength parameters compared to traditional building blocks. For the sake of the environment, it is necessary to test oil blocks in terms of the release of substances that are hazardous to the environment. In this study the process of producing oil blocks was optimized and construction materials based on WCO were produced. The physicochemical properties, strength and phytotoxicity of oil blocks were determined. Oil blocks were obtained with used cooking oil from thermal food treatment as a binder. The process parameters to obtain solid materials based on WCO were: annealing temperature 180–220 °C, annealing time 12–20 h, mass ratio of sulfuric acid (VI) to catalyzed oil in the range of 0.03–0.27. The oil blocks contained a fixed amount of catalyzed WCO relative to the weight of the whole mixture equal to 15%. Leaching tests of harmful substances from the blocks confirmed the presence of small amounts of dibenzo[a, h]anthracene; no heavy metals were detected. More than three times the growth of shoots of Sorghum saccharatum grown in soil soaked in rainwater in which the oil blocks were immersed was observed compared to the control. Graphical abstract: Image 1